2022
DOI: 10.3390/pathogens11050548
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Molecular Epidemiology of Staphylococcus aureus from Hunters and Hunting Dogs

Abstract: Several studies have showed that a dog-to-human transmission of Staphylococcus aureus occurs. Hunting dogs do not have as much contact with their owners as dogs that live in the same household as the owners; however, these dogs have contact with their owners during hunting activities as well as when hunting game; therefore, we aimed to isolate S. aureus from hunters and their hunting dogs to investigate a possible S. aureus transmission. Nose and mouth samples were collected from 30 hunters and their 78 huntin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The licking of dog owners also serves as a potential means of transmitting S. aureus between humans and dogs and vice versa. Another study supports this by indicating few dog-to-dog and dog-tohuman transmissions of S. aureus 17 . Other authors reported the presence of S. aureus in dogs in different countries.…”
Section: The Presence Of Staphylococcus Aureus In Healthy Dogs Of The...mentioning
confidence: 75%
See 1 more Smart Citation
“…The licking of dog owners also serves as a potential means of transmitting S. aureus between humans and dogs and vice versa. Another study supports this by indicating few dog-to-dog and dog-tohuman transmissions of S. aureus 17 . Other authors reported the presence of S. aureus in dogs in different countries.…”
Section: The Presence Of Staphylococcus Aureus In Healthy Dogs Of The...mentioning
confidence: 75%
“…This has led to a strong attachment between dogs and their owners or caretakers, and therefore, pets are treated as family members 11 . Dogs have been reported to be potential sources of various zoonotic pathogens, such as S. aureus, Escherichia coli, Salmonella enterica, Klebsiella species, and Bacillus species 9,12,13,14 that are resistant to various antibiotics, including ampicillin, cephalosporin, gentamicin, enrofloxacin, methicillin, and tetracycline 10,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Since cases of MRSA infection are more widely known in humans in the community, it is not realized that transmission of MRSA from pets may occur due to frequent direct contact between humans and pets [ 16 ]. Human and animal health will be significantly affected by the MRSA outbreak in pets [ 17 ].…”
Section: Mrsa In Pet Animalsmentioning
confidence: 99%
“…In addition, several studies have revealed that MRSA in pets is mostly derived from MRSA in humans [ 16 , 44 , 128 ]. The risk of MRSA colonization is correlated with close interaction with humans and pets [ 20 ].…”
Section: Epidemiology Of Mrsa In Pet Animalsmentioning
confidence: 99%
See 1 more Smart Citation